(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Gastroesophageal reflux disease (GERD) is one of the most frequent causes of consultation in primary care and gastroenterology. Over 40 % of the general population experiences occasional heartburn and regurgitation due to GERD. It is a complex disease and physiology and pathogenesis are not yet completely defined. However, abnormalities in the lower esophageal sphincter, esophageal motility or gastric emptying can cause or worsen GERD. There are various diagnostic and therapeutic approaches; however, the use of proton-pump inhibitor fundoplication permanence and (antireflux surgery), are the most effective options.